SYSTEM ANALYSIS OF A STAGED COMBUSTION ROCKET ENGINE - Capitao Patrao, Alexandre (My University, 2013)
The ability to accurately simulate how liquid rocket engines react at the system level with changing component parameters is important for a company like GKN Aerospace. Information from system performance models and trade-off studies can be used for focusing product development, evaluating the competition, and as a decision support tool when negotiating with business partners and customers. The project has three distinct deliverables; the first one is a functional description of a staged combustion rocket engine, for which the Space Shuttle Main Engine (SSME) has been chosen. The second deliverable is a steady state performance model capable of simulating and producing realistic results, and the third deliverable is a trade-off study which analyses how the system performance changes with changing component parameters. The first deliverable of the project was carried out as a literature study. The second and third parts used the information gathered in the literature study to build a performance model with a software called EcosimPro, which is a tool used to simulate transient systems described with differential-algebraic equations (DAE), ordinary differential equations (ODE) or discrete events. The project used the European Space Propulsion System Simulation (ESPSS) libraries to build the performance models. The project used a bottom-up approach for the system modelling, beginning with separate simulations of all components, and then synthesising increasingly larger engine models, until reaching a system model of the SSME. Due to lack of time and various modelling challenges, the project did not result in a functioning performance model of the complete SSME. A performance model was built, but the simulations never reached a satisfactory operating point. Results were obtained for a pseudo-cycle which contains most of the major components, in particular the high pressure turbomachinery, preburners, and thrust chamber. The results showed good coherence (maximum 6 % error) with reference data for the preburner and thrust chamber components. Unfortunately, the modelled turbine components did not deliver enough power, resulting in a maximum error of 20 %. The mixed quality of the results suggests that more effort has to be invested into the modelling of the SSME turbines and understanding how to properly achieve startup on a rocket engine as complex as the SSME. The current ESPSS libraries are too complex for design and trade-off studies, and the required startup makes modelling increasingly challenging and time-consuming. There is a new library under development, named STEADY, which will be more appropriate for the type of studies this project aimed for. Key words: Staged combustion rocket engine, system modelling, EcosimPro, ESPSS.
Keywords: Farkostteknik; Rymd- och flygteknik; Strömningsmekanik; Mekanisk energiteknik; Vehicle Engineering; Aerospace Engineering; Fluid mechanics; Mechanical energy engineering